Relational Missiology. When Mission Gets In Between - Vellguth, Klaus (Annales Missiologici Posnanienses, 2023)
The addressees of the mission of the Church today cannot be defined in terms of territorial. As a result of numerous theological discussions, an interesting expression emerged that reflected the dynamics of the mission – missio inter gentes. The preposition communicating inter indicates a specific relationship between the mission of the Church and its addressees. Missiology, which examines the nature of the mission focuses on its relatedness and hence becomes an advocate a relational theology also relational understanding of faith, religion, ecclesiology and dialogue because God gets in between.